Genetic analysis of weak expression of ABO blood group antigens in neonates - YANG Jiali; ZHAO Ding; LI Wei; ZHANG Xiaopan; LI Zhihao; TIAN Dongdong (Zhongguo shuxue zazhi)
[Objective] To perform genetic analysis on samples with weak agglutination and mixed agglutination of ABO blood group antigens in neonates, and to investigate the molecular biological characteristics of ABO subtypes in neonates. [Methods] Serological identification of ABO blood group was performed by tube method and microcolumn gel method. The ABO exons 2-7 were amplified by PCR, and the amplified products were sequenced by Sanger sequencing method to determine the genotype. [Results] Among the ABO blood group serological results of 14 neonates, 8 cases showed weakened A antigen, and 6 cases showed weakened B antigen. Seven samples were identified with ABO subtype alleles, with genotypes as A102/B101+c.538C>T, Aw26/B102, A205/O02, A205/B101(2 cases), Aw26/O02, B(A)06/O01, B101/O01(3 cases), A102/O01(2 cases), A102/B101 and B101/O02. Additionally, three other family members were also found to carry B(A)06 allele in a pedigree investigation. [Conclusion] For samples showing weakened antigens in ABO blood type identification of neonates, it is necessary to consider the possibility of ABO subtype in addition to age factors, and genetic testing can be used to prevent missed detection of ABO subtypes in neonates.